2016
DOI: 10.1245/s10434-016-5381-2
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Vascular Resection and Reconstruction in Surgery for Hilar Cholangiocarcinoma: With Special Reference to Hepatic Arterial Resection and Reconstruction

Abstract: CRR of the HA was considered efficacious in selected patients; however, long-term outcomes of the VR-A group seem unsatisfactory. Treatments additional to surgery may be necessary in cases requiring CRR of the HA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 32 publications
3
61
1
Order By: Relevance
“…No differences in morbidity rates were observed in most of the published studies (17)(18)(19)(20)(21)(22)25,(27)(28)(29)46), as it was the case in the present series. Only one study showed significantly increased morbidity rates when a PVR is performed (23).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…No differences in morbidity rates were observed in most of the published studies (17)(18)(19)(20)(21)(22)25,(27)(28)(29)46), as it was the case in the present series. Only one study showed significantly increased morbidity rates when a PVR is performed (23).…”
Section: Discussionsupporting
confidence: 61%
“…The reported portal vein thrombosis rates after curative-intent surgery for PHC with PVR in the previous series vary between 0% and 10% (17,22,23,25,26,30,45) and appears to be significantly higher compared with the patients without a PVR (30). In the present series of patients with a PVR, the portal vein thrombosis rate was 9.5%, not significantly different from the group of patients without a PVR.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Compared with the HA, the PV is relatively easy to include in combined resection and reconstruction such as wedge resection is also simpler (19), so invasion to the PV is no longer considered a contraindication for surgery and is less important than the evaluation of arterial invasion. Vascular invasion of the HA is still a contraindication and combined resection and reconstruction of the HA is technically challenging (20). From the results of our study, we consider surgery when the tumor is close to the HA on CT but no obvious encasement is visualized on convex EUS.…”
Section: Discussionmentioning
confidence: 97%